Capability of BIM application in improving the effeciency of green building project in Klang Valley - a literature review / Siti Fatimah Subki and Mashanim Mahazir - Subki, Siti Fatimah; Mahazir, Mashanim (2018)
There are countless issues regarding unsustainability activities from irresponsible bodies, where, sustainable development is needed in the event of global climate changes, air pollution, water pollution and others. Due to that, construction industry has taken this issue seriously and has come out with an idea of “green building”. Along with the existence of modern technologies, it is true that technological innovation does play an important role in both short and long term in societal, economic and also environment. In order to enhance the performance of Green Building construction, the construction industry can apply Building Information Modeling (BIM) in their project. The aim of this paper is to enhance the existing knowledge towards green building. For this paper there are about 15 research papers published within the past 7 years which are used in abstracting all the relevant literature, analyzing and coming out with the findings on what are the indicators in identifying the benefits and factors of BIM application towards green building project.